The Keldysh formalism in the time-dependent density-functional theory - Korostilv, A. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім. Г.Є. Пухова НАН України, 2010)
We have considered application the Keldysh formalism in time-dependent
density functional theory. It is shown that effects of electron-electron interaction can
be taken systematically into account in the framework of the Kadanoff-Baym
equations for Green functions determined on the Keldysh contour for the second-order
47
self-energy approximation. With the help of these Green functions we have derived
the time-dependent Kohn-Sham potential from an action functional. The Keldysh
formalism in a similar way leads to response functions that obey the causality
principle that is illustrated on the case of the time-dependent optimized effective
potential equations.